The Criminalization of Polyamory Perspective Islamic Penal Law and Indonesian New Penal Code - Bachri, Syabbul; Samuri, Mohd Al Adib; Moosa, Najma; Duran, BÃ¼ÅŸra Nur; Ramadhita, Ramadhita (AL-ISTINBATH : Jurnal Hukum Islam, 2023)
Regardless of the social stigma faced, polyamory has become a widely discussed issue and has received much attention in various fields. This study aims to examine the legal aspects regarding the criminalization of polyamory from the perspective of Islamic criminal law and the new penal code in Indonesia. This study is a type of normative juridical research with a conceptual and statutory approach. The research results show that any sexual relation outside of legal marriage is considered adultery in Islam, requiring criminal sanctions for the perpetrators. Polyamory cases involving same-sex couples are also included in the criminal act. In the Indonesian legal context, although the term polyamory is not mentioned explicitly, the new Penal Code has the potential to criminalize polyamorous perpetrators with the latest regulations regarding adultery and cohabitation offenses. This new penal code can also criminalize homosexual behaviour including lesbian, gay, bisexual, transgender, and Queer plus(LGBTQ+) people. However, the perpetrator of polyamory can only be convicted if there is a complaint from the aggrieved party (i.e. the legal spouse, children, and parents of the perpetrator), because those articles fall into the category of absolute complaint offenses. Looking at the cultural values of Indonesian society, especially the teachings of Islam as a religion adhered to by the majority of citizens, the criminalization of polyamory should be included in the ordinary complaint offense so that it can be in line with the living norms in society.